Structural and Vibrational Characterizations of Alizarin Red S - Catalan, Cesar A. N.; Justino, Licinia L. G.; FAUSTO, RUI; ILDIZ, GÜLCE ÖĞRÜÇ; Brandan, Silvia Antonia (MDPI, 2025)
In this work, the structures of the isolated anion and anhydrous and monohydrated sodium salts of alizarin red S (ARS) have been theoretically investigated within the density functional theory framework (B3LYP/6-311++G** calculations). The combination of calculations with the scaled quantum mechanics force field (SQMFF) methodology has allowed the assignment of the experimental infrared spectrum of ARS in the solid phase and the determination of the corresponding force constants. The structural analysis also included the investigation of the NMR and UV-visible spectra of the compound in solution in light of the undertaken quantum chemical calculations, the obtained theoretical data being in good agreement with the corresponding experimental ones. The impact of the presence of the Na+ counterion and hydration water on the properties of the organic ARS- fragment was evaluated. Atoms in molecules theory (AIM) analysis was also undertaken to obtain further details on the electronic structure of the investigated species, and the HOMO-LUMO gap was determined to evaluate their relative reactivity. Globally, the results obtained in this work extend the available information on alizarin red S and may also be used for the fast identification of the three studied species of the compound investigated (anhydrous and monohydrated sodium salts and isolated anion).
Keywords: Alizarin Red S; DFT Calculations; Harmonic Force Fields; Molecular and Electronic Structure; Vibrational Analysis